2020
DOI: 10.3390/en13246520
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-Polymer Interactions in a Combined Enhanced Oil Recovery Flooding

Abstract: The traditional Enhanced Oil Recovery (EOR) processes allow improving the performance of mature oilfields after waterflooding projects. Chemical EOR processes modify different physical properties of the fluids and/or the rock in order to mobilize the oil that remains trapped. Furthermore, combined processes have been proposed to improve the performance, using the properties and synergy of the chemical agents. This paper presents a novel simulator developed for a combined surfactant/polymer flooding in EOR proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 46 publications
(66 reference statements)
0
18
0
Order By: Relevance
“…There is a growing body of literature [ 11 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] endorsing the need to utilize a combination of EOR methods to obtain further benefits, which would translate into additional oil being recovered. We focus here on the synergistic effects of nanomaterials and alkali as a novel EOR formulation.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature [ 11 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] endorsing the need to utilize a combination of EOR methods to obtain further benefits, which would translate into additional oil being recovered. We focus here on the synergistic effects of nanomaterials and alkali as a novel EOR formulation.…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption in artificial brine was attributed to the presence of the positively charged cation sodium ions (Na+) in the solution that enhanced the overall electrostatic interactions between the henna extract/SDS and the quartz sand . Belhaj et al found that adsorption was improved on a negatively charged surface in the presence of salt.…”
Section: Resultsmentioning
confidence: 99%
“…The need for EOR is very urgent because of the shortage of oil resources, and it is expected that most of the oil will be produced by EOR in the future. [1][2][3][4][5] Engineers need to choose a reasonable and effective oil displacement method. 6,7 However, the original oil recovery methods, such as primary and secondary oil recovery, are only suitable for shallower reservoirs and lighter heavy oils.…”
Section: Introductionmentioning
confidence: 99%